‘Cultural Insights into Adults’ Hearing Awareness and Personal Listening Device Habits: A Survey Study - AlOmari HM; Bani Hani H; Alhanbali S; Aladasi Z; AlMasri M (Journal of Multidisciplinary Healthcare, 2024)
Hala M AlOmari,1 Hanady Bani Hani,1 Sara Alhanbali,1 Zainab Aladasi,1 Mohammad AlMasri2 1Department of Hearing and Speech Sciences, University of Jordan, Amman, Jordan; 2Department of Audiology and Speech Pathology, Al-Ahliyya Amman University, Amman, JordanCorrespondence: Hala M AlOmari, Email h_omari@ju.edu.joObjective: The aim of this study was to investigate adults’ habits regarding personal listening devices (PLDs), associated factors such as tinnitus and hearing threshold shift, and their knowledge of safety measures, including the use of hearing protectors in noisy environments.Design: A cross-sectional survey was designed and distributed online.Study Sample: Participants between the ages of 18 and 40 years were invited to complete the survey. The online survey was filled out by 274 individuals with an average age of 24.2 years (SD= 5.1 years). Based on age, the participants were grouped into young adults (18– 23 years old, 151 participants) and adults (24– 40 years old, 123 participants). The estimation of noise exposure was calculated based on self-reported responses of PLD use. Two categories emerged from this calculation: the participants with exposure lower than 80 dB were in the low exposure category (N: 196, 62.9 dB), while the participants with exposure higher than 80 dB were in the high exposure category (N: 78, 89.9 dB).Results: Based on the age categories, most of the questionnaire answers were similar between the young adults and the adults, revealing similar habits in using their PLDs. However, the investigation based on exposure revealed differences, as the participants with high exposure levels were more likely to have hobbies that involved noise, and they were less likely to obtain hearing evaluations. Among the participants, 30% used their devices at the maximum volume level and on a daily basis. 33.5% reported experiencing worsening in hearing, 2.4% reported persistent tinnitus, 94.1% knew that hearing protectors were available but only 20.7% reported using hearing protectors.Conclusion: The study concludes that adults are at risk of hearing loss due to unsafe listening habits. A discrepancy between knowledge and practice is apparent and needs to be addressed in young adults by increasing awareness of hearing loss, hearing protection and annual hearing evaluation.Keywords: recreation, noise exposure, tinnitus, listening habits, hearing protectors